INDONESIAN DITRANSITIVITY FROM COGNITIVE SEMANTICS PERSPECTIVE - Fithri, Ayyuhatsanail (Universitas Gunadarma, 2024)
This study explores Indonesian ditransitive verbs from a cognitive semantics perspective, focusing on how language reflects conceptual structures and cognitive processes in social interactions, communication, and knowledge transfer. Indonesian ditransitive constructions embody conceptual metaphors and image schemas derived from sensory-motor experiences, such as the Source-Path-Goal schema, which illustrates the transfer of entities or information from a source to a goal through a path. These constructions assign semantic roles to participants, reflecting their roles in the conceptual event represented by the verb and grounded in primitive cognitive concepts called proto-roles. Embodied cognition emphasizes the role of bodily experiences in shaping linguistic expressions, evident in how ditransitive constructions embody social interactions like giving, telling, or teaching. By analyzing cognitive models of communication and learning, Indonesian ditransitive verbs illuminate the dynamics of expertise, social hierarchies, and power dynamics. Prototype theory suggests that ditransitive verbs form categories around prototypical instances, representing fundamental social actions involving the transfer of entities or information. Overall, this study showcases how cognitive semantics provides a comprehensive framework for understanding Indonesian ditransitive verbs and their role in shaping cognitive processes and social interactions.